Upaya Peningkatan Literasi anak melalui Edukasi dan Inisiasi Pojok Baca Inovatif - Aning Az Zahra; Annis Azhar Suryaningtyas; Reza Edwin Sulistyaningtyas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
The problem of gadget addiction among children in Paremono Village had caused a decline in reading interest and weakened the culture of literacy. This community service activity aimed to improve children's literacy through education on the wise use of gadgets and the initiation of an innovative reading corner. The implementation methods included socialization, education for parents and children, and training on the administration and management of the reading corner for the TP-PKK of Paremono Village. The evaluation was carried out through pre-tests and post-tests to measure the participants’ knowledge improvement. The results showed a significant increase in understanding and skills in managing the reading corner, as well as greater parental awareness in guiding their children’s gadget use. In addition, the introduction of an innovative reading corner equipped with video books attracted children’s interest in reading and learning interactively. The storytelling activity aimed to instill literacy values and reduce gadget dependency. Overall, the program contributed to improving children’s literacy levels.